Development of a rating scale for objective assessment of performance in laparoscopic appendicectomy surgery. Issue 7 (26th March 2022) - Sirimanna, Pramudith; Boyce, Stephen; Gunanayagam, Prashanth; Gladman, Marc A.; Naganathan, Vasi
Abstract: Backgrounds: Laparoscopic appendicectomy (LA) is the most common index procedure for junior surgical trainees. Despite the shift towards competency‐based training, there is no method of quantitatively assessing performance during LA. This study aimed to obtain expert consensus regarding the items required to create a LA Rating Scale (LARS). Methods: A list of steps required for LA surgery, as well as descriptors of "poor", "average" and "excellent" performance for each of these steps were created for potential inclusion into an objective assessment tool for LA surgery. Using a Delphi method, 20 experts from multiple institutions rated on a Likert scale from 1 to 5 the suitability of these steps and descriptors of performance. Responses were obtained until consensus (Cronbach's α  > 0.8) was achieved. Results: Fifteen experts participated in the study. Consensus was achieved for all items during the first iteration of the Delphi with a Cronbach's α of 0.96. The Cronbach's α for the steps was 0.87 and 0.92 for the descriptors of performance. Steps and descriptors of performance that >80% of experts rated as ≥4 were used to create the final LARS tool. Conclusion: Multi‐institutional expert consensus was obtained regarding the steps and, for the first time, descriptors of performance for LA, demonstrating their face and content validity, as well as generalisability. Subsequently, the LARS tool was created that can be used to quantitatively assess intra‐operative performance. This instrument can be used to identify weaknesses in performance and facilitate deliberate practice, thus shifting training in LA to a competency‐based approach. Abstract : Multi‐institutional expert consensus was obtained regarding the steps and descriptors of performance for laparoscopic appendicectomy surgery, demonstrating their face and content validity, as well as generalisability. Subsequently, the Laparoscopic Appendicectomy Rating Scale was created that can be used to quantitatively assess intra‐operative performance. This tool provides an objective method of assessing performance and can be utilised within competency‐based training programs for trainees to track their progress, evaluate areas that require improvement and be credentialed for independent practice.